Investigation of charring rate for solid Malaysian timber in 2-d standard fire exposure using finite element modelling approach / Lannie Francis ... [et al.] - Francis, Lannie; Beng Hong Kueh, Ahmad; Ahmad, Zakiah (2024)
The study aims to examine the fire behaviour and char formation of Malaysian timber under two- dimensional (2-D) standard fire conditions through finite element simulations. Utilising Abaqus software and transient thermal analysis, a finite element model (FEM) was constructed and validated against furnace fire tests conducted on Resak timber beams. The results indicate that the charring rate of Resak timber below 0.55 mm/min, demonstrating better fire resistance compared to charring rate stated in Eurocode 5 standards. Notably, there is a close alignment between numerical and experimental findings, with only a 3% variance observed. Using finite element analysis to investigate the charring rate could be a cost-effective technique in studying Malaysian tropical timbers under varied fire loading conditions.